THE SOCIO-PSYCHOLOGICAL IMPACT OF DISTANCE LEARNING SYSTEM ON STUDENTS' PERSONALITY (International Educators Conference, 2025)
This article explores the socio-psychological effects of the distance learning system on students' personality development. With the rapid expansion of online education due to technological advancements and global challenges such as the COVID-19 pandemic, the traditional learning environment has undergone significant transformation. While distance learning offers flexibility, independence, and opportunities for self-development, it also presents challenges such as reduced social interaction, feelings of isolation, and a decline in motivation and self-esteem. These factors particularly affect students who lack strong social support or psychological resilience. The paper highlights the need for supportive strategies, including psychological counseling, group activities, and motivation-enhancing programs, to ensure students' healthy social and emotional adaptation in virtual learning environments.